The Effect of Education Using Video Learning Multimedia on Increasing Knowledge of Early Breastfeeding Initiation and Breastfeeding Techniques in Postpartum Sectio Caesarean Mothers at the Hospital - Rizki, Fathia; Dhini, Wahyuni Novitasari (Jurnal Kesehatan Metro Sai Wawai, 2024)
Introduction: Excusive breastfeeding begins as early as possible from birth through the implementation of maternal compassionate care and join care. However, due to the impact of the COVID-19 pandemic, there is no joint care between babies and mothers after normal or section secaria deliveries in hospitals. It is important to increase knowledge of breastfeeding techniques to mothers, especially mothers giving birth by section secaria to prevent babies from not being breastfed early. Purpose: This study to evaluate the effect of education using video learning multimedia on increasing knowledge about breastfeeding and breastfeeding techniques in mothers who give birth sectio secaria. Methods: One group pretest posttest quasi experiment design was chosen as the research design. The study involved 58 participants selected using consecutive sampling technique. The treatment group was given an educational intervention on lactation management utilising multimedia videos that had been developed with eligible validity and reliability. Statistical analysis to test the hypothesis used the Wilcoxon test with a significance level (α) of 0.05. Results: A total of 57 out of 58 participants showed an increase in knowledge about breastfeeding and breastfeeding techniques with an average score of 67.97 (pretest) increasing to 82.34 (posttest). There was an effect on the level of knowledge before and after being given education using multimedia video learning media on participants (p=0,0001). Conclusion: The use of multimedia video learning media as education can improve knowledge about breastfeeding and breastfeeding techniques in postpartum SC mothers during the COVID-19 pandemic. Clinical midwives and health supervisors can utilise this media which is easy to use both online and offline for education, so that maternity mothers are motivated to carry out early breastfeeding of newborns to continue to provide exclusive breastfeeding. Latar Belakang: Pemberian ASI ekskusif dimulai sedini mungkin sejak lahir melalui implementasi asuhan sayang ibu dan rawat gabung. Namun, dampak pandemi COVID-19 tidak dilakukan rawat gabung antara bayi dan ibu pasca bersalin normal maupun section secaria di rumah sakit. Pentingnya peningkatan pengetahuan teknik menyusui kepada ibu, khususnya ibu melahirkan secara section secaria untuk mencegah bayi tidak diberikan ASI sejak dini. Tujuan: Penelitian ini bertujuan mengevaluasi pengaruh edukasi menggunakan video learning multimedia terhadap peningkatan pengetahuan tentang pemberian ASI dan teknik menyusui pada ibu bersalin sectio secaria. Metode: Studi quasi experiment design one group pretest posttest dipilih sebagai rancangan penelitian. Penelitian melibatkan 58 partispan diseleksi menggunakan teknik consecutive sampling. Kelompok perlakuan diberikan intervensi edukasi menggunakan video multimedia dan yang telah diuji validitas dan reabilitasnya eligible. Analisis statistic untuk menguji hipotesis menggunakan wilcoxon test dengan tingkat kemaknaan (α) 0,05. Hasil: Sebanyak 98,28% dari 58 partisipan menunjukkan peningkatan pengetahuan mengenai pemberian ASI dan teknik menyusui dengan skor rata-rata 67,97 (pretest) meningkat menjadi 82,34 (posttest). Ada pengaruh level pengetahuan sebelum dan sesudah diberikan edukai menggunakan media video learning multimedia pada partisipan (p=0.0001). Simpulan: Pemanfaatan media video learning multimedia Sebagai edukasi mampu meningkatkan pengetahuan mengenai pemberian ASI dan teknik menyusui pada ibu pascabersalin SC pada masa pandemic COVID-19. Bidan klinik maupun Penyelia Kesehatan dapat memanfaatkan media ini yang mudah digunakan baik online maupun offline untuk edukasi, sehingga ibu bersalin termotivasi melaksanaan pemberian ASI dini pada bayi baru lahir hingga berlanjut memberikan ASI ekskluasif.